Identification of AmpC beta-lactamase producing clinical isolates of Klebsiella pneumoniae in Guilan and investigation of inhibitory effect of thymol on - Khorshid Jirdashtani; Fatemeh Mousavi; Leila Asadpour (نشریه دانشگاه علوم پزشکی البرز)
Introduction and objectives: Klebsiella pneumoniae is an opportunistic pathogen that plays a major role in the development of nosocomial infections. One of the most important mechanisms of resistance to beta-lactam antibiotics is the production of beta-lactamase enzymes by this bacterium. The aim of this study was to determine the frequency of AmpC beta-lactamase producing clinical isolates of K. pneumoniae in Guilan and investigating the inhibitory effect thymol on these isolates. Methods: Sixty isolates of K. pneumoniae were isolated and identified from clinical laboratories in Rasht during 2022. The pattern of antibiotic susceptibility in isolates was determined and beta-lactamase production was investigated using combined disk method. The presence of AmpC encoding genes including FOX, CITM and DHAM beta-lactamase genes in isolates was determined by PCR. The growth inhibitory effect of thymol on these isolates was determined using disck diffusion and broth microdilution and the efflux inhibitory effect was determined by Cartwheel methods. Results: Among tested isolates 46 (76.6%) showed multi drug resistant phenotype. Of the 22 phenotypically AmpC-producing isolates, CITM and DHAM genes were detected in 12 (20%) and 7 (11.66%) isolates respectively and 4 isolates had both CITM and DHAM genes at the same time. Thymol, showed growth and efflux inhibitory effects against all tested K. pneumoniae isolates. Conclusion: The results of the present study suggest the necessity of finding a successful treatment option to prevent the spread of infections caused by AmpC producing K. pneumoniae. According to the results, the use of thymol can provide a basis for the development of a new treatment against multi-drug resistant Klebsiella pneumoniae.